A Review on Photocatalysts for Water Pollutant Removal - Hiba R. Kazem; Hadeer Mohammed Subhi; Zaynab faleh Al-janahi; Hazim Y. Al- gubury (Journal of Biomedicine and Biochemistry, 2025)
Photocatalytic water filtration technology has been developed as an effective and sustainable method for removing a variety of water contaminants, including organic pollutants, heavy metals, and emerging compounds. Recent research has focused on improving the effectiveness of photocatalysts, particularly through the development of doped forms of titanium dioxide (TiO2), zinc oxide (ZnO), and nanocomposites, with the aim of enhancing light absorption, particularly in the visible spectrum. Furthermore, advances in photocatalytic reactor designs and hybrid systems that combine photocatalysis with conventional methods, such as adsorption and biological treatment, have significantly improved the efficiency of pollutant degradation.Despite these advances, the transition from laboratory-scale to industrial applications still faces several challenges, due to factors such as catalyst stability, light penetration efficiency, and economic feasibility. This study highlights current advances in photocatalyst development, reactor design, and hybrid treatment systems, while discussing key challenges and future research paths toward expanded water treatment applications.